Pengaruh Tingkat Pengetahuan dan Tingkat Pendidikan Terhadap Ketrampilan Kader Posyandu Dalam Melakukan Pijat Bayi - Farokah, Atik; Kurniasari, Eri (Malang Journal of Midwifery (MAJORY), 2022)
Baby massage is a touch therapy method for babies since ancient times. Massage belongs to the art of health care and medicine that has been practiced since ancient times. the healing touch or the art of massage provides many health benefits. This study aims to determine the effect of knowledge level and education level of Posyandu Cadres on level of baby Massage Skills in Katerban village. This study used an observational study, with a cross-sectional approach. The population for this study was 34 respondents who met the inclusion and exclusion criteria. This research was conducted on February 10- March 15 2022 in Katerban Village, Baron District, Nganjuk Regency. Data analysis used the fisher's exact test with the SPSS 21 program. The results showed that there is a relationship between level of knowledge (p value of 0.004) and level of education (p value of 0.006) to level baby massage skills. The higher the level of knowledge of Posyandu cadres will affect the skills of cadres in performing infant massage and the higher the education level of Posyandu cadres will also affect the skills of cadres in performing infant massage.